2019
DOI: 10.15252/embj.2018100882
|View full text |Cite
|
Sign up to set email alerts
|

Life‐long impairment of glucose homeostasis upon prenatal exposure to psychostimulants

Abstract: Maternal drug abuse during pregnancy is a rapidly escalating societal problem. Psychostimulants, including amphetamine, cocaine, and methamphetamine, are amongst the illicit drugs most commonly consumed by pregnant women. Neuropharmacology concepts posit that psychostimulants affect monoamine signaling in the nervous system by their affinities to neurotransmitter reuptake and vesicular transporters to heighten neurotransmitter availability extracellularly. Exacerbated dopamine signaling is particularly conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
1
13
0
2
Order By: Relevance
“…In addition to direct effects on the heart, methamphetamine exposure during gestation may promote the development of cardiovascular risk factors such as diabetes, hypertension, and obesity. A recent study by Korchynska et al ( 13 ) reported hypermethylation and decreased expression of multiple genes required for insulin production by pancreatic β cells in adult mice that were prenatally exposed to methamphetamine, amphetamine, or cocaine. This resulted in permanent impairment of insulin production and lifelong dysregulation of glucose homeostasis.…”
Section: Impact Of Prenatal Exposure To Cns Stimulants On the Adult Cmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to direct effects on the heart, methamphetamine exposure during gestation may promote the development of cardiovascular risk factors such as diabetes, hypertension, and obesity. A recent study by Korchynska et al ( 13 ) reported hypermethylation and decreased expression of multiple genes required for insulin production by pancreatic β cells in adult mice that were prenatally exposed to methamphetamine, amphetamine, or cocaine. This resulted in permanent impairment of insulin production and lifelong dysregulation of glucose homeostasis.…”
Section: Impact Of Prenatal Exposure To Cns Stimulants On the Adult Cmentioning
confidence: 99%
“…This hypothesis is speculative as we are unaware of any studies that have compared the expression levels of DAT, the norepinephrine transporter (NET), or adrenergic and dopaminergic receptors in the developing male and female fetus. Understanding the mechanism by which prenatal exposure to methamphetamine or cocaine induces sex-dependent effects in the adult heart is complicated by the fact that some methamphetamine induced effects are found exclusively in males ( 52 ) and other effects occur exclusively in females ( 13 , 27 ). Similarly, prenatal cocaine produces some effects in only in male offspring ( 26 , 28 ) and other effects that occur exclusively in female offspring ( 13 , 26 ).…”
Section: Impact Of Prenatal Exposure To Cns Stimulants On the Adult Cmentioning
confidence: 99%
See 3 more Smart Citations